Strategies for Student Evaluation in The Online Context - AVRAM, Sanda-Maria (Studia Universitatis Babeș-Bolyai Informatica, 2021)
In this paper we conducted an investigation on the performance of the students during the second semester of the academic year 2020-2021. We looked at the performance results obtained by students on the laboratory work, practical and final exams while we were forced by the Covid pandemic to move entirely into an online education system. Our focus was to determine the impact of a consistent behaviour (or lack of it) on the final student performance. We determined that, even in an online setting, a good involvement (in terms of attendance and good performance) guarantees good final results. The investigations were performed using the Formal Concept Analysis, which is a very powerful instrument already used by us in previous research in order to detect student behaviour in using an e-learning portal. Another set of results showed that the change of the final mark computation formula to be based in a higher proportion on the lab work was closer to the actual overall performance of students. Received by the editors: 9 November 2021. 2010 Mathematics Subject Classification. 68T30, 68P20. 1998 CR Categories and Descriptors. H.3.5 [Information Storage and Retrieval]:Online Information Services – Web based services; I.2.6 [Artificial Intelligence]: Learning – Knowledge acquisition; K.3.1 [Computers and Education]: Computer Uses in Education – Distance learning.